Developmental and pathological changes in the human cardiac muscle mitochondrial DNA organization, replication and copy number. - Jaakko L O Pohjoismäki; Steffi Goffart; Robert W Taylor; Douglas M Turnbull; Anu Suomalainen; Howard T Jacobs; Pekka J Karhunen (PLoS ONE)
Adult human heart mitochondrial DNA (mtDNA) has recently been shown to have a complex organization with abundant dimeric molecules, branched structures and four-way junctions. In order to understand the physiological significance of the heart-specific mtDNA maintenance mode and to find conditions that modify human heart mtDNA structure and replication, we analyzed healthy human heart of various ages as well as several different heart diseases, including ischemic heart disease, dilated as well as hypertrophic cardiomyopathies, and several mitochondrial disorders. By using one- and two-dimensional agarose gel electrophoresis, various enzymatic treatments and quantitative PCR we found that in human newborns heart mtDNA has a simple organization, lacking junctional forms and dimers. The adult-type branched forms are acquired in the early childhood, correlating with an increase in mtDNA copy number. Mitochondrial disorders involving either mutations in the mtDNA polymerase gamma (PolGalpha) or mtDNA helicase Twinkle, while having no obvious cardiac manifestation, show distinct mtDNA maintenance phenotypes, which are not seen in various types of diseased heart or in mitochondrial disorders caused by point mutations or large-scale deletions of mtDNA. The findings suggest a link between cardiac muscle development, mtDNA copy number, replication mode and topological organization. Additionally, we show that Twinkle might have a direct role in the maintenance of four-way junctions in human heart mtDNA.